MEKANISME KERJA OSTEOBLAS SAAT PENYEMBUHAN LUKA PASCA PENCABUTAN GIGI PADA PASIEN OSTEOPOROSIS (SCOPING REVIEW) - Edrizal Edrizal; Rahmi Putri Yeni Seprina (Ensiklopedia of Journal, 2021)
One of the most common dental procedures is tooth extraction. In carrying out the tooth extraction procedure, you will find several health problems, one of which is osteoporosis. Osteoporosis is a systemic bone disorder characterized by low bone mass characteristics, and there is damage to the micro-architecture of bone tissue. affect bone strength and increase the risk of bone loss. Osteoporosis is characterized by the presence of low bone mass which triggers bone fragility and increases the incidence of bone fracture. The aim of this scoping review is to find out how osteoblasts work in healing post-tooth extraction wounds in osteoporosis patients. The method in this research is using literature study method. The data was conducted through database searches of PubMed, scientist direct, and Google Scholar. The results of this scoping review are osteoblasts in bone healing after tooth extraction in osteoporosis patients who have slower than normal healing. The conclusion of this scoping review is that the healing of osteoporosis patients who underwent tooth extraction experienced a different healing from the restoration of normal tooth loss, because osteoporosis sufferers experience mineralization which causes the alveolar bone healing process to be hampered.